Xylanase production by Aspergillus versicolor - Carmona, E. C.; Pizzirani-Kleiner, A. A.; Monteiro, RTR; Jorge, J. A. (Wiley-Blackwell, 1997)
The xylanolytic system of Aspergillus versicolor is controlled by induction and carbon catabolite repression. Carboxymethylcellulose and wheat bran were the best inducers of xylanolytic activity. When the fungus was grown for 5 days on VOGEL's liquid medium with wheat bran, the optimal pH and temperature for xylanase production were 6.5 and 30 degrees C, respectively. Optimal conditions for the xylanolytic activity assay were at pH 6.0 and 55 degrees C. The half-life at 60 degrees C of the crude enzyme was 6.5 and 21 minutes, in the absence or presence of substrate, respectively.Xylan is the main hemicellulosic component of plant biomass being present in appreciable quantities in agricultural and several agroindustrial wastes. From the products of xylan enzymatic hydrolysis it is possible to obtain cell protein, fuels and other chemicals. Xylanases combined with cellulase could have applications in food processing. Cellulase-free xylanases can be also utilized for preparation of cellulose pulps and liberation of textile fibres (WOODWARD 1984; BIELY 1985, WONG et al. 1988). In view of the potential applications of xylanases, a study of these enzymes from various sources and their multiplicity is desirable.Among xylanolytic microorganisms, filamentous fungi have been more extensively studied and the genus Aspergillus has been shown to be an efficient producer of xylanases. Preliminary observations from our laboratory have demonstrated that a strain of Aspergillus versicolor, isolated from Brazilian soil, produced high xylanase and low cellulase levels, which is an interesting characteristic for some industrial applications. In this report we describe the production and some properties of xylanase obtained from this fungus.